The Potential Role of Probiotics (nutraceuticals) in Gut Health of Domestic Animals; an Alternative to Antibiotic Growth Promoters - NAWAB, A.; LIU, W.; LI, G.; IBTISHAM, F.; FOX, D P.; ZHAO, Y.; WO, J.; XIAO, M.; NAWAB, Y.; AN, L. (Journal of the Hellenic Veterinary Medical Society, 2019)
The term gut health is currently becoming more important for domestic animals including poultry. Gut health refers to the fundamental organ system which covers multiple positive functions like effective digestion, stabilizing intestinal microbiota, gut pH and modulation of effective immune response. Gut health depends on proper balance of microbial population. A wide range of feed and pathogen associated factors influence this balance, and adversely affect the animal health status and production performance. Antibiotic stimulators have been used in farm animals to achieve maximum production. But drug resistance and residual effects of antibiotics in animal products (milk, meat and egg etc.) have raised serious issues in human life. Therefore, The European Union (EU) has strictly banned the application of antibiotic stimulators in livestock nutrition in several others countries including China. As a result, an alternative to antibiotic growth promoters are required to support the profitable and sustainable animal production system. Probiotics as nutraceuticals has been categorized as an alternative natural feed supplement for commercial utilization. Such products have been recognized as safe feed additives in animal industry. Very few studies have comparatively described the effect of probiotics on gut health of domestic animals. Therefore, the aim of this review is not only to explore the beneficial effects of probiotics in improving gut health of domestic animals as an alternative to antibiotic growth promoters, but also to evaluate the probiotics associated health and risk factors, and to provide comprehensive scientific information for researchers, scientists and commercial producers.